Leading Islamic Schools as a Basis for Environmentally Friendly Education (Eco-Islamic Schools) - Agung Cahya; Sururin; Erba Rozalina Yulianti (al-Afkar, Journal For Islamic Studies, 2026)
This article aims to examine the concept of the Superior Islamic School as a basis for environmentally friendly education (Eco-Islamic School) and its role in integrating Islamic values ​​with the principles of environmental sustainability. This study uses a descriptive qualitative method with a library research approach, through analysis of primary and secondary sources in the form of books, journal articles, policy documents, and the Quran and Hadith that are relevant to education and the environment. The results of the study indicate that the Superior Islamic School has strategic potential in instilling ecological awareness in students through the integration of the values ​​of monotheism, khalifah, and amanah in the curriculum, the development of a green school culture, and the implementation of sustainable management and infrastructure. The Eco-Islamic School concept not only strengthens the spiritual and academic dimensions, but also forms the character of students who care about the environment as part of religious responsibility. This study concludes that the Eco-Islamic School is a relevant and contextual model of Islamic education in responding to the challenges of the global environmental crisis and supporting sustainable development goals.